China’s cultivated land threshold from the perspective of food security - ZHAO Xiaoyu, SUN Chunqiang, CUI Rongguo, CHEN Jing, ZHANG Xiaoyu, CAO Tingyu, LI Chao (Ziyuan Kexue)
[Objective] Cultivated land serves as the cornerstone of national food security. Under the background of significant changes in dietary consumption structure and population in China and the rising resources and environmental constraints, it is imperative to investigate China’s cultivated land threshold in the new era to meet diverse food and nutrition needs of Chinese residents. [Methods] This study started from measuring the annual per capita grain demand using the Prandial Balance method. On this basis, a cultivated land threshold calculation model was constructed, taking into account factors such as population, per capita grain demand, food self-sufficiency rate, and grain yield per unit cultivated area. Then, the minimum demand and deficit (or surplus) of cultivated land at the national and agroecological region levels was measured for 2021. Furthermore, the minimum demand of China’s cultivated land in 2035 and 2050 was predicted based on the grain yield per unit cultivated area and population change. [Results] (1) China’s annual per capita grain demand ranges from 420.0 kg to 497.1 kg in 2021. (2) According to the cultivated land threshold calculation model, per capita threshold of cultivated land in 2021 ranges from 0.07 hm2 to 0.09 hm2. The minimum demand of China’s cultivated land in 2021 ranges from 105.2534 million hm2 to 125.3017 million hm2. Cultivated land deficit and surplus in agroecological regions reflect obvious regional differences. Cultivated land surplus in Northeast China is the highest, while cultivated land deficit in areas south of the Yangtze River and South China is the highest. Cultivated land surplus decreases and cultivated land deficit increases with the rise of per capita grain demand. (3) Under the premise that the current grain yield per unit cultivated area is unchanged, minimum demand of China’s cultivated land is expected to be between 101.4168 million hm2 and 120.7342 million hm2 in 2035, and 95.3361 million hm2 and 113.4953 million hm2 in 2050. [Conclusion] Given the current rate of cultivated land reduction, it is expected that the amount of cultivated land might drop below the high value of cultivated land minimum demand by 2035. In 2050, the amount of cultivated land in China can only be sufficient to meet the minimum demand of cultivated land under the medium level annual per capita grain demand. The challenges faced by China’s cultivated land protection is very serious. In order to ensure the security of cultivated land resources in different regions of China, we should continue to implement and improve the most strict cultivated land protection system and the most strict system for conservation and intensive use of land in China; scientifically identify the policy unit of cultivated land protection based on agroecological areas; and implement targeted measures for cultivated land protection for different regions based on their resource endowments. Besides, a cross-regional, multi-level collaborative system of cultivated land protection should be established according to the spatial distribution of cultivated land surplus and deficit in combination with the construction of main functional regions.